Genomic predictors of radiation response: recent progress towards personalized radiotherapy for brain metastases - Paul M. Harary; Sanjeeth Rajaram; Maggie S. Chen; Yusuke S. Hori; David J. Park; Steven D. Chang (Cell Death Discovery)
Abstract Radiotherapy remains a key treatment modality for both primary and metastatic brain tumors. Significant technological advances in precision radiotherapy, such as stereotactic radiosurgery and intensity-modulated radiotherapy, have contributed to improved clinical outcomes. Notably, however, molecular genetics is not yet widely used to inform brain radiotherapy treatment. By comparison, genetic testing now plays a significant role in guiding targeted therapies and immunotherapies, particularly for brain metastases (BM) of lung cancer, breast cancer, and melanoma. Given increasing evidence of the importance of tumor genetics to radiation response, this may represent a currently under-utilized means of enhancing treatment outcomes. In addition, recent studies have shown potentially actionable mutations in BM which are not present in the primary tumor. Overall, this suggests that further investigation into the pathways mediating radiation response variability is warranted. Here, we provide an overview of key mechanisms implicated in BM radiation resistance, including intrinsic and acquired resistance and intratumoral heterogeneity. We then discuss advances in tumor sampling methods, such as a collection of cell-free DNA and RNA, as well as progress in genomic analysis. We further consider how these tools may be applied to provide personalized radiotherapy for BM, including patient stratification, detection of radiotoxicity, and use of radiosensitization agents. In addition, we describe recent developments in preclinical models of BM and consider their relevance to investigating radiation response. Given the increase in clinical trials evaluating the combination of radiotherapy and targeted therapies, as well as the rising incidence of BM, it is essential to develop genomically informed approaches to enhance radiation response.